Sultan Agung's Cultural Insights: Reflections of Javanese Insights - *Zaid Munawar; Sucipto Sucipto (Riwayat: Educational Journal of History and Humanities, 2022)
Sultan Agung is the greatest king in the Islamic Mataram Kingdom. He is not only talented in politics and economics, but also in the cultural arena. This article aims to examine the cultural insight of Sultan Agung in the Islamic Mataram Kingdom. That is how Sultan Agung's efforts in developing Javanese culture are closely related to Islamization in Java. This study uses a qualitative approach and historical methods. The results of the study show that Sultan Agung's cultural insight reflects the insight of the Javanese who are always willing to accept the entry of cultural elements from outside to enrich the culture they already have. With his insight, Sultan Agung was able to integrate Javanese culture with foreign culture. Among the cultural products developed by Sultan Agung are: creating legitimacy of genealogies connected to great figures, such as the Prophet Adam, the gods, the puppet king, to the king of Majapahit; create legitimacy of king titles, such as Penembahan Agung, Susuhunan, Sultan, and Khalifatullah Sayyidin Panatagama; establish a government position structure based on Islam through the Penghuluan Institution (Reh Pangulon); developing Javanese literature and language in the form of chronicles and Gendhing literature; developing the art of building, carving, painting, and music with a blend of Hindu and Islamic elements; revive the Sekaten Celebration which has developed since pre-Islamic times by updating its ceremonial equipment; and created the Javanese Islamic Calendar.